Effect of warm-up and flexibility treatments on vertical jump performance - Church, J. B.; Wiggins, M. S.; Moode, F. M.; Christ, R. (The Journal of Strength and Conditioning Research, 2001)
Although different warm-up and flexibility routines are often prescribed before physical activity, little research has been conducted to determine what effects these routines have on athletic performance in activities. The purpose of this investigation was to determine to what degree different warm-up routines affect performance in the vertical jump test. The 40 female participants were asked to perform a general warm-up only, a general warm-up and static stretching, and a general warm-up and proprioceptive neuromuscular facilitation (PNF) on 3 nonconsecutive days. Each of the treatments was followed by a vertical jump test. A 1-way repeated-measures analysis of variance revealed a significant difference in vertical jump performance. A post hoc analysis revealed decreased vertical jump performances for the PNF treatment group. Based on the results of this study, performing PNF before a vertical jump test would be detrimental to performance.